The Role of Digital Technology in Mathematics Learning and its Impact on Learning Concepts - Ardyan, Noor Romadhon (Aksioma Education Journal, 2024)
The development of digital technology has brought significant impact in mathematics learning, providing opportunities to improve the effectiveness and interactivity of the teaching and learning process. This study aims to explore the role of digital technology in mathematics learning and analyze its impact on learning concepts. This research uses a qualitative descriptive approach to understand the role of digital technology in mathematics learning and its impact on learning concepts. The data in this study were collected through literature study from various academic sources, such as scientific journals, textbooks, educational articles. The results show that digital technology has a very significant impact on mathematics learning. Whether in the aspect of improving students' understanding or transforming teaching methods, the use of technology is one of the main factors in modernizing education. It helps students understand complex mathematical concepts through a more interactive and visual approach, making it easier for different types of learners to comprehend. The implications of this study emphasize the importance of teacher training and policies that support the integration of technology to ensure maximum utilization in mathematics education, creating a more effective and engaging learning experience.